Decision support for ore sorting and preconcentration in gold applications. Issue 1 (2nd January 2020) - Bearman, R. A.; Bowman, D. J.; Dunne, R.
ABSTRACT: Upgrading coarse feed in gold plants, through a process of selective processing, has always been of interest. The level of interest has waxed and waned over the last 30–40 years, but improvements in methods and pressure to increase the efficiency of resource utilisation, have driven greater attention. The resources in question, not simply being the orebody itself, but the requirements for energy and water and the level of intensity applied. Despite various advances in technology, the market penetration of selective coarse upgrading, either via physical means (screening, DMS) or sensors (particle or mass sorting), is still limited. In relation to gold, uptake is complicated by low concentration and the lack of commercial sensors for direct detection. In this paper, the authors examine key factors impacting the rate and degree of uptake of preconcentration in the gold sector, as it relates to particle based particle sorting and DMS.